The prevalence of HIV and it's association with termination of pregnancy at Seshego Zone 4 Clinic, Capricorn District, Limpopo Province - Molepo, Avian Mantoa (My University, 2020)
Background: In South Africa, the Choice on Termination of Pregnancy Act (CTOP) (No. 92 of 1996) promotes a woman's reproductive right and choice to have an early, safe and legal abortion. Pregnancy termination among young women constitutes a public health problem particularly in South Africa where high prevalence of abortion has been recently recorded. HIV acquisition is increased two to four-fold during pregnancy, due to biological and behavioural factors including immunological changes, hormonal changes affecting the genital tract mucosa, higher frequency of unprotected sex and incident sexually transmitted infections (STIs) during pregnancy. There is a growing interest in exploring maternal mental health effects of unintended pregnancies. However, the evidence base from a small number of available studies is characterized by considerable variability, inconsistency and inconclusive findings. Therefore, the primary objective of this study was to investigate the prevalence of HIV and its association with termination of pregnancy at Seshego Zone 4 clinic in Limpopo Province. Methodology: A cross-section descriptive retrospective review study in which convenience sampling of the records of women who terminated pregnancies was used in this study. The key variable of interest in this study was HIV results and all patients records without evidence of HIV testing, and the associated results were excluded. A self-designed data extraction tool was used to extract the data from patients records and tool covered variables such as the age of the women, educational status, marital status, occupational status, year and month of termination of pregnancy, gestational age, parity, and gravidity, method of contraceptive used, HIV status, ARV and ARV regimens. Data analysis was done using the STATA statistical software version 12 for Windows (STATA Corporation, College Station, Texas). vi Results: The mean age was 24.98 years SD±14.4 and majority of women who terminated pregnancies were in the age group 20 – 24 years at 35.7% and the least number of women who terminated pregnancies were in the age groups ≥ 40 years and ≤ 14 years at 2.3% and 0.3% respectively. Majority of the women who terminated pregnancies had parity of 1 – 2 at 47.4% followed by parity of zero at 42.3% and 3 – 4 at 9.9%. Majority of the women who terminated pregnancies were in gravida 1 at 42.8% followed by those with gravida 2 at 27.1% and those who were pregnant between the 3rd and 4th time were 26.9%. There was a statistical significance difference (p<0.001) of the use of contraceptives by age groups and also in relation to parity and similarly to gravidity. The prevalence of HIV amongst women who terminated pregnancies in the current study was found to be 11.6% and this was high in 2018 at 10.5% followed by 2019, 2015 and 2016 at 10.3%, 9.2% and 9.1% respectively. The prevalence of HIV amongst women who terminated pregnancies increased with increasing level of education from 4.1% amongst women who had primary or no educational level the followed by 9,0% and 13.6% in women who had secondary and tertiary educational level respectively. The risk of women who terminate pregnancies being HIV positive in the current study increased significantly with increasing age as older women were 1.9 times more likely to be HIV positive as compared to younger ones (p=0.004) Conclusion: The findings of this study highlight the need to address the structural socio-economic drivers of the HIV epidemic among women of child-bearing age. Women of child-bearing age in this setting have large unmet reproductive health needs. Structural interventions, such as increasing contraceptive use which may be useful for reducing the burden of unplanned pregnancies. Key concepts Human immunodeficiency virus, Acquired immunodeficiency syndrome, Termination of pregnancy, Parity and Gravidity.
Thesis (MPH.) -- University of Limpopo, 2020
Keywords: Human immunodeficiency virus; Acquired immunodeficiency syndrome; Termination of pregnancy; Parity and gravidity; Abortion; HIV (Viruses); AIDS (Disease)